Domperidone Tablet: Short Review - Sharma, Shaveta (Journal of Applied Pharmaceutical Research, 2017)
Oral route is presently the gold standard in the pharmaceutical industry where it is regarded as the safest, most economical and most convenient method of drug delivery resulting in highest patient compliance. Oral delivery of active ingredients include a number of technologies, many of which may be classified as Orodispersible tablets (ODTs). Usually, elderly people experience difficulty in swallowing the conventional dosage forms like tablets, capsules, solutions and suspensions because of tremors of extremities and dysphagia. In some cases such as motion sickness, sudden episodes of allergic attack or coughing, and an unavailability of water, swallowing conventional tablets may be difficult. Domperidon is aÃÂ  mouth dispersable tablet no sustainrelease tablet developed so far.sustain release tablet can be developed.